Variation in photosynthetic efficiency of spring barley (Hordeum vulgare ssp. vulgare) landraces - Florence, Anna Forbes (The University of Edinburgh, 2017)
Crop yields are coming under pressure to continue to grow in the face of climate change, competition, disease and pressure to reduce inputs. Photosynthetic efficiency is being targeted for improvement to increase yields. This study examined the variation in parameters of photosynthetic efficiency including canopy structure (leaf length, canopy angle, and chlorophyll content and growth rate) and gas exchange (photosynthetic rate, stomatal density and chlorophyll fluorescence) in Spring Barley (Hordeum vulgare ssp vulgare). These were first established for modern cultivars representing the most widely grown lines in the last 60 years. As cultivars are developed from a small pool of parents they may have limited genetic variation available for breeding. Landraces have been suggested as sources of variation. Using field and growth cabinet based studies the photosynthetic efficiencies of canopy structure and gas exchange were established for a range of European landraces under high and low nutrient inputs. This study demonstrated that in modern cultivars the leaf length increased with year of release from 23.2 to 29.6 cm and the chlorophyll content decreased from 46.9 to 34.8 SPAD units. Once the ear had emerged no difference was seen in canopy structure or photosynthetic rate. There was variation in landrace canopy establishment rate, leaf angle and number of leaves present within the canopy. The landraces from Northern European latitudes pushed though booting and reached full canopy establishment up to 8 days sooner than those from Southern Europe. This may be a response to a shorter growth season at Northern latitudes requiring the canopy to be established quickly. The landraces held the leaves within their canopy in a more horizontal position than the Southern European lines with leaf angle ranging from 18-45 degrees at GS39 and 31-84 degrees at GS59. This regressed negatively with temperature so it may be that a vertical canopy structure is beneficial in areas with higher temperatures. The photosynthetic rate of the landraces showed no variation but when chlorophyll fluorescence examined the efficiency of photosystem II (PSII) there was a positive regression of Fv/Fm ratio with latitude. This suggested that lines from Southern Europe were experiencing a greater stress with a ratio of up to 0.822 compared to those lines from the North with ratios from 0.767. The stomatal density of the landraces showed a large difference in ranges from 22-41 stomata between the lines. When high and low nutrient inputs were compared reductions from a ratio of 0.48 to 0.47 in Harvest Index and from 55g to 52g in 1000 grain weight were seen. The chlorophyll content of the lines was also reduced from 41.7 to 39.2 SPAD units at GS39 and from 44.9 to 39.8 SPAD units at GS59 by the reduction in nutrient inputs which may be a result of less N available for the production of chlorophyll. In conclusion there is variation present in canopy structure in European landraces that may be useful for future breeding or in identifying landrace collections which could be targeted for traits of interest in photosynthetic efficiency. These landraces may provide traits which could be used to develop cultivars which are locally adapted to climate and environmental conditions.
Keywords: spring barley; Hordeum vulgare ssp. vulgare; gas exchange efficiency; canopy structure; photosynthetic efficiency landraces; Northern European landraces; stomata; traits